Creating Strategies to Transform Traditional Management Methodologies into Effective Leadership Styles to Develop Positive Management Culture - Rajput, Dulari (Digital Repository of Theses - SSBM Geneva, 2024)
In today's dynamic organizational environment, shifting from disaster management to positive leadership styles can foster positive growth, increase employee satisfaction, and improve all organizational functions. This doctoral study explores the development of a comprehensive plan designed to translate management practices into effective leadership. Good and valuable information for research and studies. Examines the effects of poor management practices such as authoritarianism, micromanagement, and punishment on organizational culture, morale, and productivity. It also explores the benefits of effective leadership, which include consensus, empowerment, collaboration, and effective communication. Having successful leadership. These include creating a culture of trust and transparency, investing in leadership development, implementing strategic initiatives and supporting cost management. Apply a leadership style that encourages innovation, creativity and team spirit. Recommendations include training plans, educational programs, and integrating psychological concepts into leadership. A scalable model can be adapted to a variety of business and organizational settings. These findings are fueling a broader discussion about leadership development and providing insight for employees who want to foster a positive, successful organization. Poor management, micromanagement, and poor communication can lead to poor employee performance, high productivity, and low productivity. This strategic plan emphasizes effective leadership development, including a focus on teamwork, teamwork, effective communication, and team development. The leadership process includes effective steps for organizational leaders to transition from poor management to effective leadership, including training, having a culture rich in feedback, creating open and inclusive communication, and creating processes that recognize and reward positive behaviours. The strategic plan was tested through pilot projects in selected organizations, and the results showed significant improvements in employee satisfaction and productivity, and that all organizations were doing well. This research contributes to the field of behavioural psychology by providing a general guide for managers who aim to create a positive and healthy culture that will ultimately lead to long-term success and growth.